Measuring household social capital in rural Vietnam using MIMIC approach - Huynh Ngoc Chuong; Nguyen Chi Hai (Cogent Economics & Finance, 2023)
The concept of social capital has gained significant attention in recent years due to its potential for improving individual and collective well-being, and for its significance in shaping social, economic, and political structures. This study aims to measure the social capital of rural Vietnam households with data from 2008 to 2016. The authors identified different aspects of household social capital as well as social capital proxies from livelihood papers. This paper applied the fundamental theories (the resource theories and network theories to measure the household social capital in Vietnam. We propose to apply the MIMIC model (multiple indicator multiple cause model) to construct the household social capital along with integrating the indicators in both views of household social capital. Results highlight the importance of understanding the multifaceted nature of social capital, which includes different forms of social networks, social participation, and social costs. The findings suggest that participation in diverse organizations plays a vital role in the formation of household social capital. In addition, the MIMIC model shows that participation in social networks is the most important factor in the formation of household social capital. Therefore, we give some implications for the measurement as well as characteristics in the social capital of households in Vietnam. The study contributes to the existing literature on social capital by emphasizing the importance of understanding the different aspects of social capital and how they interact with each other in shaping the livelihoods of rural Vietnamese households.
Keywords: 330; MIMIC model; social capital; VARHS; Vietnam rural household